Colloidal Quasi-one-dimensional Zinc-based Semiconductor Nanocrystals - Chen, Dechao (Curtin University, 2020)
In the recent decades, colloidal nanocrystals, which also termed as quantum dots, have witnessed an extraordinary boom on the new synthesised structures and improved performances in relation to their applications. This thesis focuses on developing facile synthesis strategies, new properties and applications of the emerging colloidal quasi-one-dimensional zinc-based semiconductor nanocrystals. The novel structures have shown interesting properties with relevance to diverse applications.